Marketing Research Skills: Managers Versus Workers in Micro Business in Ondo State - Oluwatoyin Olowe, Modupe; Sunday Olowe, Temitope (British Journal of Marketing Studies, 2024)
The major purpose of this study is to compare the Marketing Research skills needed managers and workers in micro business.As firms grow more and more in global markets, the role of reliable, verifiable, timely and high quality marketing research information to support decision-making becomes increasingly indispensable. The effectiveness and usefulness of decision-making is directly connected to the broad condition of the preferred sector(s) of the global market. To obtain complete information regarding the market entails designing and completing a significant number of activities arranged in logical sequence. Marketing research is the principal means by which firms comprehend existing and potential customers. Relevant literature were reviewed with respect to general and marketing research skills. The study employed a survey research design and it was conducted in the three senatorial zone in Ondo State. The entire population comprised 739 respondents made up of 283 managers and 456 employees. The sample was made up of 400 respondents and hypotheses at 0.05 level of significance. A Likert scale made of 11 structured questionnaire items were used for data analysis. The reliability co-efficient of the instrument for the study was 0.75 which was calculated by using Guttman split-half. It was found out that there was no significant difference between the general research skill possessed by both managers and workers but the marketing research skill possessed by the managers are significantly different from that of other workers. Possession of general research skill was recommended for all (managers and workers). Marketing research skill was recommended for all managers in the micro business within Ondo State.